When jokes are not funny - Humour and abuse in elite sport - Hickey, C. (Current Issues in Sport Science, 2023)
Joking and humour are central to the daily lives and lived experiences of professional elite athletes (Hickey, 2016; Roderick, 2006). Traditionally within sport, such discourses have been accepted as back and forth joking between teammates, athletes, and coaches, and should not be taken seriously by either the recipient or antagonist (Magrath, 2016). Although joking relations are widely assumed to be harmless (Plester, 2016), their characteristics and constant presence in the lives of professional and elite athletes share unmistakable similarities to forms of abuse (Jacobs et al., 2017; Mountjoy et al., 2016).